A TAT Peptide-Functionalized Liposome Delivery Phage System (TAT-Lip@PHM) for an Enhanced Eradication of Intracellular MRSA - Kaixin Liu; Xin Lu; Xudong Guo; Yi Yang; Wanying Liu; Hongbin Song; Rongtao Zhao (Pharmaceutics)
Background: Intracellular bacteria frequently result in chronic and recurrent infections. MRSA is one of the most prevalent facultative intracellular bacteria in clinical infections. The drug resistance of MRSA and the difficulty of most antibiotics in entering cells result in a suboptimal clinical efficacy of antibiotics in the treatment of intracellular MRSA. Bacteriophages represent a promising alternative therapy in the context of the current antimicrobial resistance crisis. Nevertheless, the low efficiency of phage entry into cells and their rapid inactivation remain challenges in the treatment of intracellular MRSA using phages. The utilization of functionalized carriers for the delivery of phages into cells and their protection represents a feasible strategy. Methods: In this study, a new MRSA bacteriophage (vB_SauS_PHM) was isolated from hospital sewage, exhibiting the characteristics of short incubation period, large lytic amount, and good environmental tolerance. Subsequently, vB_SauS_PHM was encapsulated by TAT peptide-functionalized liposomes through microfluidic technology and size-exclusion chromatography (SEC), forming a phage delivery system, designated TAT-Lip@PHM. Results: The encapsulation rate of the phage by TAT-Lip@PHM was 20.3%, and the cell entry efficiency was ≥90% after 8 h. The 24 h eradication rate of 300 μg/mL TAT-Lip@PHM against intracellular MRSA was 94.05% (superior to the 21.24% and 44.90% of vB_SauS_PHM and Lip@PHM, respectively), while the mammalian cell activity was >85% after 24 h incubation. Conclusions: The TAT-Lip@PHM effectively delivered the phage into the cell and showed an excellent killing effect on intracellular MRSA with low cytotoxicity. This work provides a technical reference for the application of phages in the treatment of intracellular bacterial infection.